Promosi Kesehatan Tentang Upaya Pencegahan Anemia Dengan Jus Kurma Pada Ibu Hamil Di Kelurahan Baru Urip Lubuklinggau Utara II - Juliana, Nova; Perawati, Perawati; Nurhaliza, Syafira; Yulianti, Sri Putri; Utami, Try; Murwati, Murwati (Jurnal Pengabdian Mitra Persada, 2024)
The prevalence of anemia in the world is estimated at 9% in developed countries and 43 percent in developing countries (Amaris & Rachman, 2022). The World Health Organization (WHO) (2013) states that anemia is one of the health problems worldwide, especially in developing countries and often occurs in pregnant women who are one of the populations with a disproportionate rate of anemia (Rizki et al., 2022; Aisah et al., 2022). Pregnant women need a minimum of iron in a TTD preparation of 90 tablets during pregnancy. However, the success rate of consuming Fe tablets is not optimal because of the mother's disobedience factor in consuming it for various reasons such as being lazy to take it, forgetting, nausea after consuming it. TTD preparations can be replaced by consuming foods high in iron and folic acid, one of which is dates. Consuming dates can be varied in other forms such as juice. At the end of the process of making Fresh Date Juice to Prevent Anemia, pregnant women in RT 2 Batu Urip Village can understand and understand about the content or benefits of Dates. The methods used in promotion about anemia are lectures and questions and answers as well as distributing leaflets. Then the method of making date juice used is by direct practice of making date juice. The results of the activities of making fresh date juice to prevent anemia in Pregnant Women and Young Women in RT 2 Batu Urip Village, which is the average pre-test knowledge of pregnant women and young women before the practice of making date juice is <50 in the less category. Then the average post-test knowledge of pregnant women and young women after the practice of making date juice is >50 in the good category.